Construction and characterization of mutants of Salmonella typhimurium deficient in DNA repair of O6-methylguanine. - Yamada, M (1995)
Escherichia coli has two O6-methylguanine DNA methyltransferases that repair alkylation damage in DNA and are encoded by the ada and ogt genes. The ada gene of E. coli also regulates the adaptive response to alkylation damage. The closely related species Salmonella typhimurium possesses methyltransferase activities but does not exhibit an adaptive response conferring detectable resistance to mutagenic methylating agents. We have previously cloned the ada-like gene of S. typhimurium (adaST) and constructed an adaST-deletion derivative of S. typhimurium TA1535. Unexpectedly, the sensitivity of the resulting strain to the mutagenic action of N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) was similar to that of the parent strain. In this study, we have cloned and sequenced the ogt-like gene of S. typhimurium (ogtST) and characterized ogtST-deletion derivatives of TA1535. The ogtST mutant was more sensitive than the parent strain to the mutagenicity of MNNG and other simple alkylating agents with longer alkyl groups (ethyl, propyl, and butyl). The adaST-ogtST double mutant had a level of hypersensitivity to these agents similar to that of the ogtST single mutant. The ogtST and the adaST-ogtST mutants also displayed a two to three times higher spontaneous mutation frequency than the parent strain and the adaST mutant. These results indicate that the OgtST protein, but not the AdaST protein, plays a major role in protecting S. typhimurium from the mutagenic action of endogenous as well as exogenous alkylating agents.